PENGARUH PDRB, JUMLAH PENDUDUK DAN PENGANGGURAN TERHADAP KEMISKINAN DI KOTA BANJARMASIN - SEPTIANA SEPTIANA; Rusdiansyah Rusdiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Septiana 2018 “This reasearch to find out ‘bout the influence of pdrb, population and unemployment to poverty Banjarmasin city year 2002-2016”. Poverty is a problem that has not been resolved to date even though several government efforts have been made to reduce poverty. In this study we can see how big the poverty level and which factors affect poverty so that we can find solutions and policies appropriate to overcome poverty in the city of Banjarmasin. The scope of this study covers poverty conditions in Banjarmasin using time series data by analyzing for 15 years. The method of analysis used is multiple linear regression analysis method. By using R-Square Test (R2), Simultaneous Test (F Test) and Individual Test (t test). The result of the research of the influence of pdrb, population and unemployment together have an effect on to poverty. pdrb and unemployment have no significant effect on poverty. While the number of residents significantly influence the poverty in the city of Banjarmasin. The most dominant factor affecting poverty is the population.Keywords: Economic, Poverty, GDP, Population and Unemployment.